The relationship between physical activity intensity and domains with cardiac autonomic modulation in adults: An observational protocol study - Tebar, William R. [UNESP]; Ritti-Dias, Raphael M.; Saraiva, Bruna T. C. [UNESP]; Gil, Fernanda C. S. [UNESP]; Delfino, Leandro D. [UNESP]; Damato, Tatiana M. M. [UNESP]; Aguilar, Beatriz A. S. [UNESP]; Silva, Stéfany C. B. [UNESP]; Mota, Jorge; Vanderlei, Luiz Carlos M. [UNESP]; Christofaro, Diego G.D. [UNESP] (Wolters Kluwer, 2019)
Introduction:Cardiac autonomic modulation is an important marker of cardiovascular health and the practice of physical activity is a fundamental tool for good maintenance or increments in this marker. However, it is not clear in the literature whether different intensities and different domains of physical activity are related in the same way to cardiac autonomic modulation.Objectives:This randomized epidemiologic study will examine the relationship between cardiac autonomic modulation and different intensities and domains of physical activity in a representative sample of adults.Methods:The sample of study will consist of 252 subjects aged from 18 years and above. The sample will be randomized through census sectors in which the neighborhoods, streets, and houses will also be randomized. Cardiac autonomic modulation will be assessed by heart rate variability and the intensity (mild, moderate, intense) of physical activity will be evaluated by means of accelerometers, while the different domains of physical activity (physical activity at work, occupational activities) will be evaluated through a questionnaire. The relationship between cardiac autonomic modulation and different physical activity intensities, as well as the different domains will be analyzed by linear regression, considering a statistical significance of 5% and a 95% confidence interval. This research protocol is registered in ClinicalTrials.gov at number NCT03986879.
Keywords: autonomic modulation; autonomic nervous system; heart rate variability; motor activity; physical activity